(untitled) (Journal of Environmental Microbiology and Toxicology, 2014)
The aim of this study is to isolate a new luciferase gene from Photobacterium strain MIE by using specific polymerase chain reaction (PCR) and to identify whether this new Photobacterium sp. same strain as P.kishitanii or P.phosphoreum. The Photobacterium strain MIE was successfully isolated, characterized and identified in 2012. After analyzing by using blastn of 16S rRNA, this strain was closely related with several Photobacterium kishitanii and Photobacterium phosphoreum strain. Primers were designed based on the nucleotide multiple sequence alignment of luciferase gene from several Photobacterium from both species deposited in Genebank. Luciferase genes from P.kishitanii and P.phosphoreum have the expected size of 1.8 kbp and 2.1 kbp, respectively. Result shown that, both size were amplified by using specific primers